Ideology and Pragmatism: Discourse Factors in Infrastructure Development in Indonesia’s Jokowi-JK Era - Ekayanta, Fredick Boven (Jurnal Politik, 2019)
The discussion about development discourse in a country talking about how an idea affect economic policies. In Indonesia, the development discourse continues to change depending on the ruling regime. After the reformation, the dominant discourse is a neoliberal one that minimizes the role of the state in development. During the reign of Jokowi-JK, however, the role of the state strengthened. The government plans to build a massive infrastructure of the physical economy. The government legitimized its choice of action as the implementation of the Pancasila and Trisakti ideologies. Using the theories of Ernesto Laclau and Chantal Mouffe, this article argues that the state legitimizes its policies as implementing ideology by building infrastructure development discourse, but covers only pragmatic practices that occur. The practices themselves are pragmatic because the government ignored the fate and rights of citizens affected by infrastructure development.